Unique and atypical deletions in Prader–Willi syndrome reveal distinct phenotypes - Kim, Soo-Jeong; Miller, Jennifer L; Kuipers, Paul J; German, Jennifer Ruth; Beaudet, Arthur L; Sahoo, Trilochan; Driscoll, Daniel J (European journal of human genetics : EJHG, 2012)
Prader-Willi syndrome (PWS) is a multisystem, contiguous gene disorder caused by an absence of paternally expressed genes within the 15q11.2-q13 region via one of the three main genetic mechanisms: deletion of the paternally inherited 15q11.2-q13 region, maternal uniparental disomy and imprinting defect. The deletion class is typically subdivided into Type 1 and Type 2 based on their proximal breakpoints (BP1-BP3 and BP2-BP3, respectively). Despite PWS being a well-characterized genetic disorder the role of the specific genes contributing to various aspects of the phenotype are not well understood. Methylation-specific multiplex ligation-dependent probe amplification (MS-MLPA) is a recently developed technique that detects copy number changes and aberrant DNA methylation. In this study, we initially applied MS-MLPA to elucidate the deletion subtypes of 88 subjects. In our cohort, 32 had a Type 1 and 49 had a Type 2 deletion. The remaining seven subjects had unique or atypical deletions that were either smaller (n=5) or larger (n=2) than typically described and were further characterized by array-based comparative genome hybridization. In two subjects both the PWS region (15q11.2) and the newly described 15q13.3 microdeletion syndrome region were deleted. The subjects with a unique or an atypical deletion revealed distinct phenotypic features. In conclusion, unique or atypical deletions were found in ∼8% of the deletion subjects with PWS in our cohort. These novel deletions provide further insight into the potential role of several of the genes within the 15q11.2 and the 15q13.3 regions.